Evaluation of Alternative Antioxidants for Poultry Nutrition: Fractionation of Cashew Seed Shells (Anacardium occidentale L.) to Improve Poultry Health, in Vitro - Andi Musmalika; Sri Purwanti; Wempie Pakiding (Journal of Global Innovations in Agricultural Sciences, 2025)
Cashew nut has antioxidant potential with high level of polyphenols, as plant-based antioxidant. This research aims to examine the in vitro fractionation of cashew nut shells as a product that has potential as a source of antioxidants. The treatment consisted of 2 treatments and 3 replications. The treatments used were: P1 (Cashew nut shell fraction with concentrations 80, 160, and 320 ppm), P2 (Vitamin C control concentrations 80, 160, and 320 ppm). The parameters observed in this study were the organoleptic extract, the content of phytochemical compounds in the form of phenol and flavonoid content, antioxidant activity and antioxidant enzyme activity of cashew seed shells, with the resulting output being that the cashew seed shell fraction has a phenol content of 160 mg/g and flavonoids of 300 mg/g, the higher the phenol and flavonoid content. The higher level of activity as an antioxidant, was in accordance with the results of the antioxidant test of the cashew nut shell fraction which has an antioxidant content at a strong level with an IC50 value of 99.459. However, the SOD enzyme content is at a weak level with an IC50 value of 206.250 ppm. The catalase enzyme is at a moderate level with an IC50 value of 121,493 ppm, and in the GPx enzyme content test it is at a weak level with an IC50 value of 279,143 ppm. Keywords: Cashew nut shells, antioxidants, SOD enzyme, catalase enzyme, GPx enzyme.